Comparative Gut Proteome of Nyssomyia umbratilis from Leishmaniasis Endemic and Non-Endemic Areas of Amazon Reveals Differences in Microbiota and Proteins Related to Immunity and Gut Function - Antonio Jorge Tempone; Guilherme Ian Spelta; Victor Ramos de Almeida; Daniel Machado Giglioti; Erika Moutinho Costa; Izabela Mathias; Helena Vargas; Thais Lemos-Silva; Ana Carolina Pedro dos Santos Ribeiro; Eric Fabrício Marialva; Cláudia Rios-Velasquez; Michel Batista; et al. (Microorganisms)
The northern region of Brazil is endemic for American Tegumentary Leishmaniasis (ATL) primarily caused by Leishmania guyanensis and transmitted by the sand fly Nyssomyia umbratilis. The disease occurs at different rates in the municipalities of Manacapuru (MAN) and Rio Preto da Eva (RPE), located in the state of Amazonas. Despite their geographic proximity and separation by the Rio Negro, MAN has a low incidence, whereas RPE reports a significantly higher number of cases. Since the vector is present in both locations, potential biological differences in N. umbratilis may influence transmission. Previous studies suggested genotypic and phenotypic differences in N. umbratilis from both localities. To investigate the molecular factors underlying their potentially differential vectorial capacities, we performed a comparative proteomic analysis of dissected insect intestines from both localities. Our results revealed that sand flies from MAN showed a higher abundance of proteins related to gene transcription, protein translation, amino acid and proton transport, innate immune response and intestinal motility. Since the importance of microbiota has previously been shown in parasite–vector interactions, we also identified bacteria from both vector populations. We detected bacteria specific to each population and, exclusively in MAN, some species described in the literature as having parasiticidal properties. These findings highlight molecular and microbial peculiarities that could contribute to the observed difference in ATL prevalence in the two areas.